Re-operation for recurrent intracranial meningioma – is it worth it?. (15th October 2021) - Richardson, George; Gillespie, Conor; Mustafa, Mohammad; Taweel, Basel; Millward, Christopher; Islim, Abdurrahman; Jenkinson, Michael
Abstract: Aims: Meningioma is the commonest primary brain tumour. Despite surgery, meningiomas can recur. Surgery is usually the first line treatment for recurrent meningioma. The aim was to determine the risk factors associated with clinical outcomes (performance status, morbidity, mortality, recurrence) following re-operation for recurrence of intracranial meningioma. Method: Retrospective cohort study (1998-2018). Eligible patients had re-operation for local recurrence of a previously operated meningioma. Collected data included baseline clinical and imaging characteristic. Primary outcome measure was performance status after each re-operation. Secondary outcome measures were medical and surgical morbidity, recurrence-free survival (RFS) and overall survival (OS). Results: Fifty-eight patients were eligible (38 female, mean age at 1st re-operation 56 years (SD=11.4)). Eleven patients (18.9%) had 2 re-operations and 3 patients (3.4%) had 3 re-operations. Median follow up was 125.5 months (IQR 73-191.5). Median time to 1st recurrence and 1st re-operation were 36.5 (IQR 24.2–79.1) and 43.8 months (IQR 22.9–102.7), respectively. Fifteen patients (25.9%) had worse performance status after 1st re-operation, compared to 6.9% (n=4) after the primary operation (Figure 1). Complication rate was 32.8% (n=19) after the primary operation compared to 46.6% (n=27) after 1st re-operation. At primary operation, there were 29 (50%) grade 1, 26 (44.8%) grade 2, and 1 (1.7%) grade 3 tumours. Median RFS after first re-operation was 68 months (95% CI 45.5-90.5) (figure 2). Median OS was 312 months (95% CI 236.9-387.1) (Figure 3). Post-operative complications were a risk factor for worsened performance status following re-operation (OR 4.91, 95% CI 1.3-18.4). Conclusion: Re-operation is associated with a worse performance status and increased risk of complications. Re-operating meningiomas for radiological recurrence without symptoms increases patient morbidity. Shared-care management decision should be made with patients when considering operating for radiological recurrence only.